2001
DOI: 10.1002/app.2061
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐state carbon‐13 NMR study of material composites based on sugarcane bagasse and thermoplastics polymers

Abstract: ABSTRACT:The composites formed by sugarcane bagasse and thermoplastic polymers, such as polypropylene (PP), polyethylene (PE), and ethylene-co-vinyl acetate (EVA), have been analysed by carbon-13 high-resolution solid-state nuclear magnetic resonance (NMR), employing crosspolarization magic angle spinning (CPMAS); variable contact-time experiment and proton spin-lattice relaxation time in the rotating frame. NMR responses showed that these techniques can be used to observe the degree of compatibility and homog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…In some sense, the reverse of this process is the analysis of whole plants and parts of plants grown in controlled conditions to determine where 13 C enrichment occurs (142) or the examination of the genetically modified trees to determine chemical changes that can be detected with NMR spectroscopy (143). In one interesting twist, composites of sugarcane bagasse with thermoplastics were analyzed with NMR spectroscopy (144).…”
Section: Biological Solidsmentioning
confidence: 99%
“…In some sense, the reverse of this process is the analysis of whole plants and parts of plants grown in controlled conditions to determine where 13 C enrichment occurs (142) or the examination of the genetically modified trees to determine chemical changes that can be detected with NMR spectroscopy (143). In one interesting twist, composites of sugarcane bagasse with thermoplastics were analyzed with NMR spectroscopy (144).…”
Section: Biological Solidsmentioning
confidence: 99%
“…Essa técnica permite a caracterização das interações moleculares existentes entre os componentes da fibra natural [1,2] . Somando, a relaxometria por RMN é uma técnica importante para caracterização de materiais [3,4] .…”
Section: Introductionunclassified
“…These chemical reagents convert the hydrophilic surface of cellulosic fiber to a hydrophobic one; as a result the fiberfiber hydrogen bonding is reduced, the dispersion of the fibers in the matrix is enhanced and the adhesion is improved via the mechanism such as entanglement, mechanical interlocking and formation of physical or chemical bonds between treated fibers and the polymer matrix [5]. Stael et al [6] analyzed the composites formed by sugar cane bagasse and thermoplastic polymer such as polystyrene, polyethylene, and ethylene-co-vinyl acetate by NMR technique. NMR responses showed that in EVA composite, bagasse can act as reinforcement whereas in PS and PE composites bagasse acts as filler.…”
Section: Introductionmentioning
confidence: 99%